The Effect of Motivation, Discipline and Job Satisfaction on Employee Performance at Ud. Mha Frozen Food - Feri Prastiawan; Evi Fitrotun Najiah; Mohammad Yaskun (Jurnal Multidisiplin Sahombu, 2024)
This study aims to determine the influence of motivation, discipline and job satisfaction on the performance of UD employees. MHA Frozen food, both partially and simultaneously, as well as to find out which variables are the most dominant affecting employee performance. The population in this study is all employees at UD. MHA Frozen food in 2023 which totals 152 employees. The method of sample selection is simple random sampling. The sample of this study amounted to 110 UD employees. MHA Frozen food. This research is in the type of quantitative descriptive research. Data analysis used multiple linear regression test analysis tools, data validity and reliability test and classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Hypothesis testing was carried out with partial testing (t), simultaneous testing (f), and determination (R2). Data were processed using the Statistical Package for the Social Sciences (SPSS) version 27. The results of the study formulated the variables of motivation, discipline and job satisfaction simultaneously and partially had a positive and significant effect on the performance of UD employees. MHA Frozen food. Job satisfaction has a dominant influence on employee performance.